Chromozom 21 - specifické mikroRNA v mateřské cirkulaci: zhodnocení jejich významu pro screening Downova syndromu u plodu - Hromadníková, I; Kotlabová, K; Doucha, J; Chudoba, D; Calda, P; Dlouhá, K (Ceska gynekologie, 2012)
OBJECTIVE: Initially, we focused on the detection of extracellular microRNAs in maternal circulation, whose genes are located on human chromosome 21 (miR-99a, let-7c, miR-125b-2, miR-155 and miR-802). Subsequently, we studied if plasmatic concentrations and/or expression profile of extracellular chromosome 21-derived microRNAs would distinguish between pregnancies bearing euploid foetuses and those affected with Down syndrome. DESIGN: Pilot study. SETTING: Division of Molecular Biology and Cell Pathology, Department of Gynaecology and Obstetrics, Third Faculty of Medicine, Charles University, Prague. METHODS: 12 women with normal course of gestation (mean 16.4 weeks, median 16.0 weeks), 12 pregnancies bearing Down syndrome foetus (mean 18.2 weeks, median 18.5 weeks) and 6 non-pregnant individuals were involved in the retrospective study. RNA enriched for small RNAs (including microRNAs) was isolated from 1ml of plasma sample. Consequently relevant microRNA was transcribed into cDNA using specific stem-loop primer and detected by specific real-time PCR assay. RESULTS: Commercial systems enabled reliable detection of 4 out of 5 extracellular chromosome 21-derived microRNAs (miR-99a, let-7c, miR-125b-2 and miR-155). Expression profile of extracellular miR-99a, miR-125b-2 and miR-155 was significantly higher in the cohort of pregnant women than in non-pregnant individuals. Also plasmatic levels of miR-99a and miR-125b-2 were significantly increased in pregnant women. Unfortunately, the concentrations and gene expression of extracellular chromosome 21-derived microRNAs (miR-99a, let-7c, miR-125b-2 and miR-155) did not differ between the cohorts of pregnancies bearing euploid foetuses and those affected with Down syndrome. CONCLUSION: Analysis of extracellular chromosome 21-derived microRNAs does not distinguish between pregnancies with euploid and aneuploid foetuses and has no benefit for screening programmes.
Keywords: ženské pohlaví; Female; těhotenství; Downův syndrom; genetické markery; lidé; Chromosomes, Human, Pair 21; Humans; mikro RNA; Genetic Markers; Pregnancy; Prenatal Diagnosis; lidské chromozomy, pár 21; Down Syndrome; MicroRNAs; prenatální diagnóza